Targeting SAA expression via siRNA mitigates preterm birth induced by maternal inflammation - Lei, Jun; Liu, Yang; Liu, Jin; Liu, Anguo; Jones-Beatty, Kimberly; Enninga, Elizabeth Ann L.; Townsel, Courtney; Burd, Irina (Frontiers in Pharmacology, 2026)
IntroductionPlacental inflammation is a major contributor to preterm birth (PTB), and there are currently few targeted strategies to prevent PTB and its associated adverse neonatal outcomes. Serum amyloid A (SAA), particularly the isoforms SAA1 and SAA2, are well-recognized inflammatory markers, but their functional roles in placental inflammation remain poorly defined.MethodsUsing a translational mouse model of sub-chronic maternal inflammation, we investigated the immune mechanisms and therapeutic potential of siRNA-mediated targeting of Saa2 (siSaa2). Placental expression patterns of SAA2 were examined in vivo, and macrophage responses to extracellular SAA2 were modeled in vitro using RAW264.7 cells to assess downstream P2X7R-dependent signaling and functional outcomes.ResultsSAA2 is primarily induced in placental trophoblast and endothelial compartments during inflammation, where it acts as an extracellular inflammatory mediator. In vitro, we model macrophage responses to extracellular SAA2 using RAW264.7 cells to examine downstream P2X7R-dependent signaling and functional outcomes. Maternal administration of siSaa2 improved PTB rates, placental morphology and fetal brain development. Additionally, SAA1 and SAA2 exhibited distinct expression patterns in the mouse and human placenta.DiscussionThese findings identify placental SAA2 as a key inflammatory mediator in inflammation-associated PTB and demonstrate that targeted silencing of Saa2 represents a potential therapeutic strategy to mitigate placental injury and adverse fetal outcomes.